2018
DOI: 10.3906/sag-1712-28
|View full text |Cite
|
Sign up to set email alerts
|

e relationship between vitamin D de ciency and erythrocyte sedimentation rate in patients with diabetes

Abstract: Background/aim: Vitamin D deficiency in diabetic patients has been shown to be associated with some inflammatory markers. However, its relationship with erythrocyte sedimentation rate (ESR) is still unknown. The aim of this study was to investigate the relationship between vitamin D deficiency and ESR in patients with type 2 diabetes mellitus (T2DM). Materials and methods:This cross-sectional study was conducted with 294 consecutive patients with T2DM. Serum levels of 25-hydroxyvitamin D, glycemic parameters, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The association between vitamin D deficiency and increased risk of inflammation and respiratory infections was stated in many studies; a study by Lehouck et al 28 showed the role of high vitamin D supplements in reducing COPD exacerbations. In addition to a study conducted by Kaya et al 29 who reported the strong association between vitamin D with ESR as a marker of inflammation in diabetic patients. Furthermore, Panfili et al, 30 stated that vitamin D deficiency contributes to acute respiratory distress syndrome (ARDS), and indicated that vitamin D has a role in preventing lung fibrosis which is a common complication and a long-term concern in these patients.…”
Section: Discussionmentioning
confidence: 84%
“…The association between vitamin D deficiency and increased risk of inflammation and respiratory infections was stated in many studies; a study by Lehouck et al 28 showed the role of high vitamin D supplements in reducing COPD exacerbations. In addition to a study conducted by Kaya et al 29 who reported the strong association between vitamin D with ESR as a marker of inflammation in diabetic patients. Furthermore, Panfili et al, 30 stated that vitamin D deficiency contributes to acute respiratory distress syndrome (ARDS), and indicated that vitamin D has a role in preventing lung fibrosis which is a common complication and a long-term concern in these patients.…”
Section: Discussionmentioning
confidence: 84%
“…16 Studies have confirmed that vitamin D can have impacts on all of these pathophysiological pathways through vitamin D receptors on pancreatic β cells, skeletal muscle and adipocytes. 17 First, 1.25(OH) 2 D binds to VDRs on pancreatic β cells and directly affects insulin secretion. 18,19 In addition, 1.25(OH) 2 D can increase insulin receptor expression, activate insulin receptors and enhance insulin mediated glucose transport.…”
mentioning
confidence: 99%
“…18 In another study conducted in our country on 294 diabetic patients, vitamin D deficiency was found in 47.9% of patients and vitamin D insufficiency was found in 32.9% of patients. 19 Only 20.3% of the patients had sufficient 25(OH)D levels in our study, which indicates that 25(OH)D deficiency is still prevalent in our society and should be closely monitored and treated. Gender differences in the prevalence of 25(OH)D are controversial.…”
Section: Discussionmentioning
confidence: 58%